Lipid treatment and goal attainment characteristics among persons with atherosclerotic cardiovascular disease in the United States - Alexa C. Klimchak; Miraj Y. Patel; Şerban R. Iorga; Natasha Kulkarni; Nathan D. Wong (American Journal of Preventive Cardiology, 2020)
Objective: National estimates of atherosclerotic cardiovascular disease (ASCVD) in the United States (US) are scarce, especially for patients grouped by cardiovascular risk, lipid-lowering therapy use, and low-density lipoprotein cholesterol (LDL-C) levels. The objective of this study was to estimate the size of the ASCVD population, including the subgroup at very high risk for recurrent events as defined by the 2018 Multi-Society Cholesterol Guidelines. Methods: Patient-level data from the Truven MarketScan Research Database were used and extrapolated to approximate national figures based on known national demographic and ASCVD prevalence numbers. Demographic and clinical characteristics, including LDL-C levels and lipid-lowering therapy use, were captured. Results: The extrapolated prevalence of ASCVD in 2014 was 18.3 million, of whom 690,524 had an acute coronary syndrome event in the past year. An estimated 41.4% of patients with ASCVD had diabetes, 44.9% had polyvascular disease, and 23.8% had multiple cardiovascular events. A third of those with ASCVD were estimated to be at very high risk for subsequent events per the 2018 Multi-Society Cholesterol Guidelines. Of those with ASCVD, 74.2% were estimated to have an LDL-C level of ≥70 ​md/dL, and more than half of these patients were neither on statins nor ezetimibe. Only 9.2% of patients with ASCVD and LDL-C ≥70 ​mg/dL were on a high-intensity statin. Conclusions: The underutilization of lipid-lowering therapies in general, and in particular the relatively low usage of high-intensity statins among patients with uncontrolled LDL-C (including those at very high risk), suggests that eligible patients for proprotein convertase subtilisin/kexin type 9 inhibitor therapy may not be as numerous as previously estimated.